AUTISM SPECTRUM DISORDER IN CHILDREN: THE CRITICAL NEED FOR AN INTERDISCIPLINARY APPROACH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Autism Spectrum Disorder (ASD) is a complex, heterogeneous neurodevelopmental condition characterized by persistent deficits in social communication and interaction, alongside restricted, repetitive patterns of behavior, interests, or activities. Its prevalence has risen dramatically worldwide, posing a significant public health challenge. The etiology of ASD is multifactorial, involving a strong genetic predisposition intertwined with environmental, immunological, and metabolic factors. This complexity necessitates a move beyond a singular disciplinary perspective. This comprehensive review elucidates the clinical manifestations, diagnostic criteria according to the ICD-11, and the intricate etiological landscape of ASD. We provide a detailed analysis of contemporary management strategies, encompassing psychopharmacology for co-occurring conditions, innovative biological treatments under investigation, and evidence-based behavioral interventions. A central thesis of this article is that optimal outcomes for children with ASD are achieved only through a cohesive, patient-centered, interdisciplinary approach that integrates medical, therapeutic, educational, and family-based support systems.